A Randomized Trial Evaluating Whether Topiramate Aids Smoking Cessation and Prevents Alcohol Relapse in Recovering Alcohol‐Dependent Men. (28th December 2016) - Anthenelli, Robert M.; Heffner, Jaimee L.; Wong, Esther; Tibbs, Jessie; Russell, Katie; Isgro, Melodie; Dinh, Elizabeth; Wehrle, Chris; Worley, Matthew J.; Doran, Neal
Abstract : Background: Alcohol and nicotine dependence frequently co‐occur, and quitting smoking might enhance long‐term alcohol abstinence. Topiramate appears to help non‐alcohol‐dependent individuals quit smoking, and our pilot work suggested efficacy only in men. It also prevents relapse to alcohol in recently detoxified alcoholics. We evaluated topiramate in abstinent alcohol‐dependent men to assess whether this medication (i) promotes smoking cessation and (ii) prevents alcohol and other drug relapse in the context of smoking cessation treatment. Methods: One hundred and twenty‐nine alcohol‐abstinent (mean ~6 months) alcohol‐dependent male smokers (80% with other substance use disorders) participated in this 12‐week randomized, double blind, parallel group comparison of topiramate (up to 200 mg/d) and placebo with a 24‐week nontreatment follow‐up period. The study was carried out sequentially at 2 academic centers in the Midwest and Southern California between March 23, 2009 and November 20, 2014. All participants received manual‐guided smoking cessation counseling combined with medication‐focused compliance enhancement therapy. Randomization was block designed by the research pharmacist in a 1:1 ratio. Participants, investigators, and research personnel were masked to treatment assignment. The primary smoking end point was biochemically confirmed 4‐week continuous abstinence from smoking during weeks 9 to 12, while the secondary end point was relapse to any drinking or drug use during the entire 36‐week evaluation period. Logistic regression was used to determine the effects of topiramate on quitting smoking and alcohol relapse, controlling for relevant covariates. The trial is registered at ClinicalTrials.gov (number NCT00802412) and is now closed. Results: Only a small proportion (7.9%) of topiramate‐treated participants were able to quit smoking, and this cessation rate was similar to placebo (10.6%; odds ratio = 1.60; 95% confidence interval 0.4, 6.5; p  = 0.51). Roughly 30% of the sample had a documented relapse to drinking or drug use during the study, and these rates were similar in the topiramate (20/63; 31.8%) and placebo groups (18/66; 27.3%; p  = 0.58). Results of a longitudinal logistic regression model examining time to any alcohol relapse revealed no medication effect. Conclusions: Topiramate at a daily dosage of up to 200 mg per day, combined with smoking cessation and medication adherence counseling, had no effects on smoking cessation or the prevention of alcohol or drug relapse in male smokers who were in early or sustained full remission from alcohol and motivated to make a quit attempt. Alternative approaches for treating this high‐risk, dually dependent population are needed. Abstract : Alcohol and nicotine dependence frequently co‐occur, and quitting smoking enhances long‐term alcohol abstinence. We evaluated whether topiramate aids smoking cessation in alcohol‐abstinent male smokers who participated in a randomized controlled trial of topiramate (200 mg/d) versus placebo. Only a small proportion (7.9%) of topiramate‐treated participants were able to quit smoking, a rate similar to placebo (10.6%; p  > 0.05). We conclude that topiramate at this dosage did not aid smoking cessation in male smokers motivated to make a quit attempt.